Four new species of the Aleiodes compressor Herrich-Schäffer species-group (Hymenoptera: Braconidae: Rogadinae) from South America - Sulca, Lidia (2016)
Four new species of the Aleiodes compressor (Herrich-Schäffer) species-group from the Neotropical Region are described and illustrated: Aleiodes segakiato sp. nov. and A. lamasi sp. nov. from Peru, A. macro sp. nov. from Argentina, and A. palmito sp. nov. from Mexico. With the addition of these new species, the compressor species-group has ten known species; two from Old World, two from Nearctic Region, and six from Neotropical Region. In addition to the descriptions of the new species, a key to known species is presented, and a new distribution record for A. mantiqueirensis Shimbori, Shaw and Penteado-Dias from Ecuador is reported.